Toxicity of Substances Isolated from Helietta puberula RE Fr. (Rutaceae) to the Leaf-cutting Ant Atta sexdens L. (Hymenoptera: Formicidae) and the Symbiotic Fungus Leucoagaricus gongylophorus (Singer) Möller - Almeida, Roberta; Peñaflor, Maria; Simote, Simone; Bueno, Odair; Hebling, Maria; Pagnocca, Fernando; Fernandes, João; Vieira, Paulo; da Silva, Maria (BioAssay, 2009)
Leaf-cutting ants may be a serious pest for the agriculture and silviculture once they cut plant material to cultivate a symbiotic fungus, which is their main food source. Currently, chemical methods are largely used for controlling of these insects, but sometimes with serious damages to human health, environment and other non-target organisms as well. Considering this, some plants are promising as a source of toxic substances, which can be toxic both to leaf-cutting ants and the symbiotic fungus. The main objective of this research was to determine the toxicity of extracts, fractions and isolated substances from Helietta puberula RE Fr. (Rutaceae) to Atta sexdens L. (Hymenoptera: Formicidae) workers and their symbiotic fungus, Leucoagaricus gongylophorus (Singer) Möller. Toxicity of vegetal extracts to leaf-cutting ants were determined by ingestion bioassays, while the activity against the symbiotic fungus was evaluated by its development in a culture medium containing vegetal extracts in it. The results showed that three out of six compounds isolated from H. puberula have effectively targeted both partners simultaneously, indicating that this plant is a promising source of novel insecticidal substances for the control of leaf-cutting ants.